Glances over the New York that emerges from silence Joseph Mitchell’s memorial-essay journalism - Passos, Mateus Yuri (Folios, revista de la Facultad de Comunicaciones y Filología, 2022)
This paper discusses ‘Street Life’, ‘Days in the Branch’ and ‘A Place of Pasts’, the fragments of Joseph Mitchell’s unfinished memoir book that the reporter of The New Yorker started to write during his famous 1964-1994 silence period. Compared to the whole of Mitchell’s output, this set of texts may be seen as constitutive of a fourth period of his writing, gradually established between the mid-1940s and early 1960s. They also constitute a unique genre of journalism, here named memorial essay.